PERANCANGAN BUKU TIPOGRAFI UNTUK KEMASAN DENGAN METODE DESIGN THINKING - Erlyana, Yana; Winnie, Winnie; Veronica, Veronica (Institut Bisnis dan Teknologi Indonesia, 2023)
The appropriate utilization of typography holds substantial significance as it directly influences the visual perception of a brand. Typography serves as a visual manifestation of a brand, wherein the distinctive characteristics of each letter reflect the brand's overall image. Similarly, within the domain of packaging design, typography assumes a critical role in upholding brand identity. Recognizing the urgency of this matter, the present study endeavors to develop an informative compendium that exhibits the application of typography in packaging design through visually captivating presentations, complemented by case studies of well-known brands prevalent in the Indonesian market. Employing the design thinking methodology, which entails problem-solving through product development, this study culminates in the production of a book that showcases typographical content presented in an uncluttered layout, emphasizing the significance of typography while elucidating its contents. The study presents its findings in the form of a book showing typographical content, meticulously designed with a clean layout that highlights the exploration of typography within the book's contents. The significance of this research stems from the demand for comprehensive and visually engaging resources that demonstrate the application of typography in packaging design, aligning with the evolving requirements of the digital economy industry and the educational needs of Visual Communication Design students in Indonesia.